Navigating diversity: primer impact on arthropod recovery in molecular environmental monitoring in tropical Amazon - Penner, Fernanda Valente; Lynggaard, Christina; Argolo, Leandro Araujo; da Silva, Yorranna Kelly Rossy; de Oliveira, Guilherme Corrêa; Bohmann, Kristine; Gastauer, Markus (Frontiers in Ecology and Evolution, 2024)
IntroductionThe urgent need for effective environmental monitoring amid the escalating biodiversity crisis has prompted the adoption of molecular techniques like DNA metabarcoding. Through sequencing of taxonomically informative mitochondrial markers in bulk arthropod samples, metabarcoding allows assessment of arthropod diversity, which is crucial for ecosystem health evaluations, especially in threatened regions like the Amazon. However, challenges such as primer biases and reference database limitations persist. MethodsHere, we assess the performance of four metabarcoding primer sets, two COI markers (ZBJ-ArtF1c/ZBJ-ArtR2c [Zeale]: 157bp, targeting arthropods, and mlCOIintF/jgHCO2198 [Leray]: 313bp, targeting metazoans) and two 16S markers (Ins16S_1shortF/Ins16S_1shortR [Ins16S]: 150bp, targeting insects, and Coleop_16Sc/Coleop_16Sd [EPP]: 105bp, targeting arthropods, mainly Coleoptera) in amplifying the taxonomic constituents of bulk arthropod samples, collected across different natural and anthropogenic habitats from the Brazilian Amazon biome. To evaluate primer performance, we used the indicators (i) amplification efficiency, (ii) primer specificity, i.e., the amount of non-target sequences, (iii) detected OTU richness, (iv) group coverage and (v) taxonomic resolution. Finally, we (vi) estimated the refinement in taxa recovery by additional amplifications. ResultsDespite lower specificity and contrasting results regarding OTU richness, the primer pairs returning larger fragments showed higher taxonomic resolution (Ins16S) and broader taxonomic coverage (Leray) than Zeale and EPP did. Furthermore, results demonstrated the complementarity of the Leray and the Ins16S primer sets from taxon-dependent studies. ConclusionsDespite limitations, combining these primers could enhance biodiversity monitoring in the region. Considering incomplete reference gene banks, primers maximizing OTU richness (EPP and Leray) may be the best choice for taxon-independent surveys. These findings underscore the importance of primer selection and highlight the ongoing efforts to refine DNA metabarcoding for robust environmental assessments.